Branchial Cysts in Quito, Ecuador - Pacheco-Ojeda,Luis (2020)
Abstract Introduction Branchial cleft anomalies are the second most common congenital anomaly in children. However, some lesions may not develop clinically and are not diagnosed until adulthood. The recent literature of branchial cysts (BCs) in the adult population is really scanty. For this reason, we analyzed the clinical and surgical management of the adult population treated for a BC at a tertiary care general hospital. Methods A retrospective review of the clinical records of all the patients with histological diagnosis of BC who were surgically treated at the Social Security Hospital in Quito, Ecuador, was performed. Fifty-one patients (27 women) with congenital anomalies of the 2nd (43 patients with cysts) and 3rd (6 patients with cysts and 2 with fistula) branchial arches were diagnosed and treated. Diagnosis was made on clinical grounds and by computed tomography scan. Results The 43 patients with a 2nd branchial cleft cyst underwent complete surgical excision through a wide mid-neck transverse cervicotomy. The 6 cases of 3rd branchial cleft cyst underwent surgical resection through a lower-neck transverse incision, and the 2 patients with clinical fistula in the lower aspect of the neck were operated on via an elliptical incision around this external fistula opening. Postoperative evolution was uneventful in all patients. Conclusions Branchial cysts can occasionally be diagnosed in adult patients in the setting of a general hospital population. A correct clinical and imaging assessment was diagnostic in most patients. Complete surgical resection was curative in all our patients, and postoperative complications were exceptional.